LEGAL ASPECTS OF SOCIAL ADVERTISING AND ITS DEVELOPMENT - Yarmolenko, O. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Research Objectives. In many instances mass communication, specifically social advertising, plays a significant role in the formation of public opinion. Therefore, it is almost impossible to overstate the importance of mass media laws and regulations. In Ukraine, the Law on Advertising was reviewed and revised multiple times since it was first adopted as a part of the Constitution of Ukraine in 1996. This article is a snapshot of some key government laws and policies about advertising in Ukraine that were implemented until 2010. Definition. By the Law of Ukraine, advertisement is an information about a person or goods, disseminated in any form and by any means and is aimed at the development and maintenance of advertising consumers’ awareness and their interest related to such a person or goods [1]. Social advertising should be clearly separated from other information regardless of a form or means of its dissemination so that it could be identified as advertising. Concluding Remarks. The author of the research Oleksandr Iarmolenko suggests that in order to make social advertising more appealing to public in Ukraine, first it needs to gain the status of public policy. Furthermore, it s marketing should never be oriented to promote sales or influence political debate. Last, social advertising should not reveal its sponsors or founders; neither it should contain their trademark, brand or logo. Next Steps. The researcher argues, that social advertising should always bring about positive behavior change without being a negativity or depression trigger. It needs to be interesting, creative, understandable and motivating. The part of the Law on Advertising concerning social advertising needs to be amplified so it better regulates relations in this area thus stimulating its development